APPetite for Something New: The Katona József Library’s Mobile Application - Csapó, Noémi; Dani, Erzsébet (Central European Journal of Educational Research, 2022)
The Katona József Library of Bács-Kiskun County has always placed great emphasis on reaching out to all age groups. In order to achieve our goal, we need to be informed and up-to-date with the latest trends and to be present on as many virtual platforms as possible. That’s why, at the beginning of 2021, a few enthusiastic librarians of our institution thought that a library mobile app could be the next important milestone in our continuous development and renewal. All this experimentation and testing has finally paid off: the Katona József Library’s mobile app is available on the Google Play Store from Autumn 2021. It’s no secret that our primary goal with our entirely self-developed, in-house app was to target young people, perhaps the hardest-to-reach age group for libraries. So, in addition to creating content specifically for teens (book reviews, games), we also wanted the look and feel of the app to be coherent and dynamic. Of course, we did not want the app to replace our library’s website, but to provide content that could be enjoyed on a smaller screen. As the application is easy to navigate and use, so that older people who are generally less familiar with the digital world will have no problems using it. For those who are a little apprehensive, one of our tutorials promoting the app will give them all the help they need to become a confident user. So what does our library app do? In addition to the Programme Guide, there is a dedicated menu with a regularly updated document guide. And with our ever-expanding thematic video selection, you can watch videos of our library programmes at any time. Of course, a library mobile app would be useless without a Catalogue menu, so webOPAC is also just a click away. With our Virtual Tour, which is unique among national library mobile apps, you can even take a look around our library from the comfort of your own home, sitting in your armchair. Games were also included in the app. We have thought of games for all ages, with four to four games for children, teens and adults. Puzzles are mainly related to the world of books, but there are also some puzzles on local history. We hope that our innovation will live up to our expectations and will appeal to a wider audience than just young people. Our aim is to ensure that our application remains a popular and constantly renewing service in the long term.